Athar Barnaamij Inghimasi Lughawi Fi Tahsin Maharat Al-Tahadduth Bi Al-Lughatil Al-Arabiyyah Ladaa Al-Thulab Al-Maliziyyin Fi Al-Urdun - Muhamad Zaid, Ismail; Naseer, Maqableh (2016)
The purpose of this study was to investigate the effects of a language immersion program on improving Malaysian students' Arabic Language speaking skills. To achieve this goal, a quantitative method was used, and there is an instrument: oral test. This program has been applied, over a period of five months, on 17 first-year Malaysian students, who are studying Arabic Language and Literature at the Faculty of Arts. Yarmouk University, during the academic year (2012/2013). T-test was used for the interrelated samples (Paired Samples T-Test). The results of the study showed the impact size of this program on the speaking skills which scored 64.0%.The results also revealed statistically significant differences between the mean of pre and post tests concerning speaking skills, which equaled 8.76%. In light of the results, the researchers recommends hiring a proposed language immersion program to aid in the improvement of speaking skills and in the teaching Arabic language for non -Arabic speakers.